The Language of Employability A Corpus-Based Analysis of UK University Websites - Fotiadou, Maria (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book employs a corpus-based Critical Discourse Analysis (CDA) methodology to analyse the language used by university careers services in the UK. Drawing on a corpus which includes the public-facing websites of careers services from 24 Russell Group and 34 Post-92 universities, the author highlights some of the potentially problematic 'common-sense' views and ideas that are currently promoted to students using these services. She argues that the language used by university websites promotes neoliberal ideology and encourages the denaturalisation of such language. This book will be of interest to linguists, sociologists, education scholars, and scholars who are otherwise interested in the notion of employability. Maria Fotiadou completed her PhD at the University of Sunderland, UK. She is now an independent researcher, and her research interests are in corpus linguistics, critical discourse analysis, the discourse of employability, gender studies, language and power, ideology, and resistance.
Chapter 1. Introduction: The marketisation of Higher Education in the UK and the language of employability -- Chapter 2. Higher Education policy since the 1980s -- Chapter 3. Corpus-based Critical Discourse Analysis -- Chapter 4. Data and methods: University websites and corpus-based CDA -- Chapter 5. The representation of the job-seeking reality and the notion of employability -- Chapter 6. Understanding careers services and their roles -- Chapter 7. Similarities and differences in the language used by post-1992 and Russell Group universities -- Chapter 8. Conclusions: Denaturalising the language of employability.
Keywords: Applied linguistics; Linguistics-Methodology.; Knowledge, Sociology of; Career education; Education, Higher; Applied Linguistics; Research Methods in Language and Linguistics; Sociology of Knowledge and Discourse; Career Skills; Higher Education